Assesment of Industrial Enterprises Activities and Investment Development in Šiauliai Sity - Simanauskas, Leonas; Damašienė, Violeta (Ekonomika, 2001)
The analyses activities of the operating enterprises and amount and structure of investments in Šiauliai city. Relatively non-perspective enterprises are chemical materials and products, rubber and plastic materials, metal processing equipment enterprises. Developing industry in Šiauliai city priority should be given to branches of industry which rely on knowhow and skilled labour force. Relying on macro and micro business environment the following conclusions have been made: • due to increased competition and orientation to western markets the enterprises are focusing equally on low price and good quality production; • lack of capital investment has made a negative impact on the companies’ development, their competativeness, export volumes and foreign market increase; • as local credit and reinvestment resources are limited, the companies should focus on foreign liary; • slow industrial development in the city is predetermined by lack of clear innovative activities. Needs of enterprises for capital investments were assessed, opportunities of setting up new enterprises were defined and ways of improvement of the existing conditions were outlined, carrying out the continuous industry development strategy in Šiauliai, setting up of production enterprises orientated on science, development of enterprises of higher added value should get the priority focus.